Identifying new therapeutics for focused ultrasound-enhanced drug delivery in the management of glioblastoma - Holman, Ryan; McDannold, Nathan (Frontiers in Oncology, 2025)
Glioblastoma, a grade IV astrocytoma, typically has a poor prognosis, with most patients succumbing within eighteen months of diagnosis and few experiencing long-term survival. Focused ultrasound, an emerging localized therapy, has shown promising results in early-phase studies for glioblastoma by improving the uptake of temozolomide and carboplatin. The blood-brain barrier is critical to homeostasis by regulating the movement of substances between the bloodstream and the central nervous system. While this barrier helps prevent infections from bloodborne pathogens, it also hinders the delivery of cancer therapies to gliomas. Combining focused ultrasound with circulating microbubbles enhances local blood-brain barrier permeability, facilitating the intratumoral uptake of systemic cancer therapies. The purpose of this study was to identify promising new therapeutics in the treatment of glioblastoma for localized drug delivery via focused ultrasound. This review provides an overview of the current standard of care for newly diagnosed and recurrent glioblastoma, identifies current therapies indicated for the treatment, discusses key aspects of microbubble resonators, describes focused ultrasound devices under evaluation in human trials, and concludes with a perspective of emerging therapeutics for future studies.